Mengungkap Hukum Jaminan Konvensional dan Syariah Dalam Perjanjian Bisnis - Syaifudin, Ahmad (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
In conventional and Sharia-based business agreements, collateral serves different functions for the parties. For the debtor, collateral increases the capacity to gain the creditor's trust. For the creditor, collateral fosters confidence that the debtor will fulfil its obligations according to the agreed agreement. Consistent use of appropriate collateral institutions fosters legal certainty in making business agreements. This research uses normative juridical, conceptual and statutory approaches and descriptive analysis techniques. This research aims to find concrete legal arrangements of collateral in conventional and sharia business agreements. The results are 1) collateral law is included in the scope of private law whose existence provides legal certainty and protection for creditors as an additional agreement (accessory) regulated in Books II and III KUH Perdata, 2) rahn and kafalah are forms of collateral in sharia agreements until now still do not provide legal certainty because they use material security institutions fiducia and mortgage rights.